2006
DOI: 10.1016/j.febslet.2006.02.074
|View full text |Cite
|
Sign up to set email alerts
|

The synaptic vesicle protein 2C mediates the uptake of botulinum neurotoxin A into phrenic nerves

Abstract: Botulinum neurotoxins (BoNTs) inhibit neurotransmitter release by selectively cleaving core components of the vesicular fusion machinery. The synaptic vesicle proteins Synaptotagmin-I and -II act as receptors for BoNT/B and BoNT/G. Here we show that BoNT/A also interacts with a synaptic vesicle protein, the synaptic vesicle glycoprotein 2C (SV2C), but not with the homologous proteins SV2A and SV2B. Binding of BoNT/A occurs at the membrane juxtaposed region preceding transmembrane domain 8. A peptide comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
241
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(257 citation statements)
references
References 21 publications
12
241
0
4
Order By: Relevance
“…Subsequently, the toxin heavy chain binds its high affinity membrane protein acceptors, synaptic vesicle protein 2 (SV2) and fibroblast growth factor receptor 3, which govern BoNT/A binding and endocytotic entry into neurons (Dong et al, 2006;Jacky et al, 2013;Mahrhold et al, 2006). BoNT/A internalization into neurons may be mediated by all isoforms of SV2 (SV2 A-C), with the strongest affinity for SV2C (Dong et al, 2006).…”
Section: 3 Bont/a Internalization Into Nerve Terminalsmentioning
confidence: 99%
“…Subsequently, the toxin heavy chain binds its high affinity membrane protein acceptors, synaptic vesicle protein 2 (SV2) and fibroblast growth factor receptor 3, which govern BoNT/A binding and endocytotic entry into neurons (Dong et al, 2006;Jacky et al, 2013;Mahrhold et al, 2006). BoNT/A internalization into neurons may be mediated by all isoforms of SV2 (SV2 A-C), with the strongest affinity for SV2C (Dong et al, 2006).…”
Section: 3 Bont/a Internalization Into Nerve Terminalsmentioning
confidence: 99%
“…[13][14][15][16] Studies on cultured hippocampal neurons from the rat or mouse phrenic nerve of the hemidiaphragm have shown that BTX-A recognizes and enters the ganglioside during neurotransmitter exocytosis when more-active receptors are exposed, exploiting the secretory vesicle recycling pathway. 17,18 Thus, endocytosis of BTX-A is enhanced by synaptic activity. 17,19 Once internalization has occurred, the BTX-A activity remains within the vicinity of the nerve terminal.…”
Section: Binding and Internalizationmentioning
confidence: 99%
“…Each NT recognizes a distinct receptor. Synaptotagmin II associated with ganglioside G T1b has been assigned as protein receptor of BoNT/B and BoNT/G, and synaptic vesicle membrane protein SV2 as receptor of BoNT/A (Nishiki et al, 1994(Nishiki et al, , 1996Rummel et al, 2004a;Dong et al, 2006;Mahrhold et al, 2006). Specific cell surface receptors account for the different sensitivity of cells and animal species to BoNTs and TeNT and play a major role in the subsequent intracellular trafficking.…”
Section: Transcytotic Pathway and Gangliosides: The Case Of Clostridimentioning
confidence: 99%